ANALISIS PENANAMAN NILAI-NILAI KARAKTER PADA SISWA SEKOLAH DASAR (STUDI EKSPLORASI MEMBENTUK BUDI PEKERTI LUHUR DAN AKHLAK PADA SISWA SD) - Desi Fitriana Rahmawati; Dian Kusumawati; Ade Bagus Primadoni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The research aims to examine the implementation of character education in shaping students’ noble character and moral behavior at SD Muhammadiyah Sukorejo. The research is motivated by the decline in students’ character values influenced by globalization, digital culture, and the weakening of moral habituation in the school environment. Data collection techniques were carried out through observation, interviews, and documentation involving the principal, class teachers, and fifth grade students. Data analysis techniques used interactive analysis consisting of data reduction, data presentation, and drawing conclusions. Results indicate that character values instilled include social responsibility and spiritual responsibility, which are implemented through daily habituation activities, teacher role modeling, Integrating Islamic principles into educational activities and school culture. Supporting factors include a religious school environment, consistent teacher exemplification, and strong institutional commitment, while Factors hindering progress include disparities in students' family conditions and a lack of parental participation. In general, the implementation of moral education at Muhammadiyah Sukorejo Elementary School contributes positively to shaping students who demonstrate discipline, responsibility, religiosity, and noble character.